2014
DOI: 10.1371/journal.pone.0094521
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem in Hearing-Impaired Children: The Influence of Communication, Education, and Audiological Characteristics

Abstract: ObjectiveSufficient self-esteem is extremely important for psychosocial functioning. It is hypothesized that hearing-impaired (HI) children have lower levels of self-esteem, because, among other things, they frequently experience lower language and communication skills. Therefore, the aim of this study was to compare HI children's self-esteem across different domains with those of normal hearing (NH) children and to investigate the influence of communication, type of education, and audiological characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 45 publications
4
55
0
1
Order By: Relevance
“…Although our results show no impact on diagnosis of hearing problems, we do find that the UPK policy leads to higher probability of receiving treatment for hearing problems. Prior research has suggested that hearing problems may negatively impact academic performance, self-esteem, and social functioning (Daud et al, 2010;American Speech-Language-Hearing Association, 2017;Theunissen et al, 2014) and that early intervention is essential for closing the developmental gap (Mellon et al, 2009). In fact, students who are treated for hearing problems in childhood and receive school-based support can develop communication skills on par with or above their healthy peers by adolescence (Eriks-Brophy et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Although our results show no impact on diagnosis of hearing problems, we do find that the UPK policy leads to higher probability of receiving treatment for hearing problems. Prior research has suggested that hearing problems may negatively impact academic performance, self-esteem, and social functioning (Daud et al, 2010;American Speech-Language-Hearing Association, 2017;Theunissen et al, 2014) and that early intervention is essential for closing the developmental gap (Mellon et al, 2009). In fact, students who are treated for hearing problems in childhood and receive school-based support can develop communication skills on par with or above their healthy peers by adolescence (Eriks-Brophy et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…to develop more social and emotional problems than hearing peers [13][14][15][16][17]. For example, DHH children experience a lower quality of life and more mental health problems such as anxiety, depression, and behavioral problems than their peers without hearing loss [18][19][20][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…However, younger age of hearing aid implantation and existence of cochlear implants at longer period of time expressed higher levels of their perceived self-esteem. 26 A comparative study on perceived self-esteem was conducted between D/HH individuals who are actively or inactively participating in sport-related activities using the Rosenberg self-esteem scale (RSES). Higher RSES scores indicate a more positive feelings about the self.…”
Section: Discussionmentioning
confidence: 99%